Characteristics and patients’ portrayals of Norwegian social media memes. A mixed methods analysis - Jarmund, Anders Hagen; Tollefsen, Sofie Eline; Ryssdal, Mariell; Jensen, Audun Bakke; Sakshaug, Baard Cristoffer; Unneland, Eirik; Solberg, Berge; Mjølstad, Bente Prytz (Frontiers in Medicine, 2023)
Background. Despite reports on troublesome contents created and shared online by healthcare professionals, a systematic inquiry of this potential problem has been missing. Our objective was to characterize the content of healthcare-associated social media memes in terms of common themes and how patients were portrayed. Material and methods. This study applied a mixed methods approach to characterize the contents of Instagram memes from popular medicine- or nursing-associated accounts in Norway. In total, 2 269 posts from 18 Instagram accounts were included and coded for thematic contents. In addition, we conducted a comprehensive thematic analysis of 30 selected posts directly related to patients. Results. . A fifth of all posts (21%) were related to patients, including 139 posts (6%) related to vulnerable patients. Work was, however, the most common theme overall (59%). Nursing-associated accounts posted more patient-related contents than medicine-associated accounts (p < 0.01), but the difference may be partly explained by the former focusing on work life rather than student life. Patient-related posts often thematized (1) trust and breach of trust, (2) difficulties and discomfort at work, and (3) comical aspects of everyday life as a healthcare professional. Discussion. We found that a considerable number of Instagram posts from healthcare-associated accounts included patients and that these posts were diverse in terms of contents and offensiveness. Awareness that professional values also apply online is important for both healthcare students and healthcare providers. Social media memes can act as an educational resource to facilitate discussions about (e-)professionalism, the challenges and coping of everyday life, and ethical conflicts arising in healthcare settings.